DAMPAK STRUKTUR MODAL DAN SALES GROWTH TERHADAP KINERJA PERUSAHAAN - Furniawan; D. Muhamad Yamin (Universitas La Tansa Mashiro, 2025)
Financial performance is an analysis that is carried out to see how far a company is in carrying out its business by using existing rules regarding proper and correct financial implementation. Therefore, financial performance can be said to be the achievement of the company in a period that describes the condition of the company's financial health with indicators of capital adequacy, liquidity and profitability. The method of determining the sample using purposive sampling, with several specified criteria, obtained 14 samples of retail companies with a total of 70 financial report data. To answer the research problem and test the research hypothesis, multiple linear regression analysis techniques are used and the SPSS 20 application is used. The results of the study show that capital structure (DER) has a negative and significant effect on firm performance (ROA). Sales growth (Sales Growth) has a positive and significant effect on company performance (ROA). Capital structure (DER) and sales growth (Sales Growth) have a positive and significant effect on company performance (ROA). It is suggested to further researchers to expand the sample of companies listed on the Indonesia Stock Exchange (IDX), and also to use capital structure variables using the Debt to Asset Ratio (DAR) proxy to measure the ratio between total debt and total assets and have more influence on Return on Assets (ROA) to improve company performance.